Confronting obstacles to inclusion : international responses to developing inclusive education - Rose, Richard, 1953-; National Association for Special Educational Needs (Great Britain). (London : Routledge, 2010)
'Addresses interpretations of inclusive education by drawing upon the experiences and expertise of leading writers and academics who have direct experience of teaching and researching this area around the world'--Publisher description.
Understanding inclusion: interpretations, perspectives and cultures / Richard Rose -- Confronting obstacles to inclusion: how the US news media report disability / Beth Haller, Sue Ralph, and Zosia Zaks -- 'They say the grass is blue': gypsies, travellers, and cultural dissonance / Chris Derrington -- Including'children with special needs' in the Indian education system: negotiating a contested terrain / Nidhi Singal -- Family perspectives: parents in partnership / Mithu Alur -- Supporting parents and families in the development of inclusive practice / Garry Hornby -- The role of schools in establishing home-school partnerships / Rob Ashdown -- Valuing and learning from young people / Michael Shevlin -- Engaging young children in research about an inclusion project / Phyllis Jones and Ann Gillies -- Beyond tokenism? Participation and'voice' for pupils with significant learning difficulties / Hazel Lawson -- Teacher education for inclusion / Chris Forlin -- Promoting teacher development for diversity / Leena Kaikkonen -- Teacher's professional learning and inclusive practice / Lani Florian and Martyn Rouse -- Developing inclusive approaches to teaching and learning / Meng Deng -- Overcoming barriers to the acquisition of literacy in twenty-first-century inclusive classroom / The McPhillips, Sheena Bell and Mary Doveston -- The development of inclusive teaching and learning: a European perspective? / Amanda Watkins and Cor Meijer -- Supporting students with disabilities in inclusive classrooms: personnel and peers / Michael F. Giangreco ... [et al.] -- Identifying core competencies and skills for assistants: implications for training to support inclusive classrooms / {u2069}ne O'Neill -- Classroom support for including students with challenging behaviour / Sue Roffey -- Building on ideas and maintaining a dialogue for change / Richard Rose.
'A David Fulton book.'
Published in association with NASEN.
Includes bibliographical references and index
Keywords: Inclusive education; Special education